About The Meaning And The Importance Of “Velâyetname” In View Of Ahmet Yesevi Haci Bektaş Veli (Journal of Alevism-Bektashism Studies, 2010)
“In the article the emphasis is on the sources of mistakes in the perception of Alevism-Bektashism. It is reported that beliefs has social and cultural roots and the lack of informations arising from lack of acknowledgement of these social and cultural roots are now creating serious problems It is emphasized that although the fight for personal advantages are having a certain in.fiuence, It is necessary to know/learn Ahmet Yesevi ve Yesevism, Şeyh Safi ve Erdebil Dergahand that Velayetname should be studied also from this perspective.”